Evaluation of skeletal muscle DTI in patients with duchenne muscular dystrophy. (9th October 2015) - Hooijmans, M. T.; Damon, B. M.; Froeling, M.; Versluis, M. J.; Burakiewicz, J.; Verschuuren, J. J. G. M.; Niks, E. H.; Webb, A. G.; Kan, H. E.
<x xml:space="preserve">Abstract</x> Diffusion tensor imaging (DTI) is a popular method to assess differences in fiber organization in diseased and healthy muscle tissue. Previous work has shown that muscle DTI measurements depend on signal‐to‐noise ratio (SNR), %fat, and tissue T2. The goal of this study was to evaluate the potential biasing effects of these factors on skeletal muscle DTI data in patients with Duchenne Muscular Dystrophy (DMD). MR images were obtained of the right lower leg of 21 DMD patients and 12 healthy controls on a Philips 3T system. DTI measurements were combined with quantitative in‐vivo measures of mean water T2, %fat and SNR to evaluate their effect on DTI parameter estimation. All outcome measures were determined within ROIs drawn for six lower leg muscles. Between group analysis, using all ROIs, revealed a significantly elevated FA in the GCL, SOL and PER muscles (p<0.05) and an increased mean diffusivity (p<0.05) and λ3 (p<0.05) in the TA muscle of DMD patients. In‐vivo evaluation of the individual confounders showed behaviour in line with predictions from previous simulation work. To account for these confounders, subsequent analysis used only ROIs with SNR greater than 20. With this criterion we found significantly greater MD in the TA muscle of DMD patient (p<0.009) and λ3 in the TA and GCL muscles (p<0.001) of DMD patients, but no differences in FA. As both increased %fat and lower SNR are expected to reduce the apparent MD and λ3, these between‐group differences are likely due to pathophysiology. However, the increased FA, observed when using all ROIs, likely reflects the effect of low SNR and %fat on the DTI parameter estimation. These findings suggest that measuring mean water T2, %fat and SNR is essential to ascribe changes in DTI measures to intrinsic diffusion changes or to confounding influences. Copyright © 2015 John Wiley & Sons, Ltd.